Bibliometric Analysis and Systematic Literature Review in Management Practices & Artificial Intelligence - BOUDRAA , Chaymae; HELMI , Driss (Revue Internationale des Sciences de Gestion, 2024)
Artificial Intelligence (AI) has emerged as a transformative technology to reshape different practices of management, such as decision-making processes, organizational performance, and human interactions in business settings. The purpose of this study is to map out the intersection between Artificial Intelligence and Management practices. Several studies of relevant scholarly articles have been carried out to identify the interaction of AI on the three main Management practices through a comprehensive review analysis using Scopus database. This bibliometric study offers insights into scientific trends, author patterns and thematic field advancement. In addition to pointing out the gaps in the literature and suggesting directions for future research such as the ethical issues surrounding the use of AI. The results of the systematic literature review are eventually mapped out on VOSviewer and presented by visualization techniques demonstrating key research clusters. This study is subject to limitations as it solely depends on the Scopus database. Future studies could grant from merging additional sources like PubMed, Crossref, among others.